Recycling of phosphate mine tailings for the production of geopolymers. (1st June 2018) - Moukannaa, S.; Loutou, M.; Benzaazoua, M.; Vitola, L.; Alami, J.; Hakkou, R.
Abstract: Phosphate sludge is a fine by-product produced with large quantities during ore phosphate beneficiation (washing and flotation), and deposited in surface impoundment without treatment, which create environmental issues. The main objective of this study was to investigate the potential reuse of phosphate sludge as a partial replacement of fly ash and metakaolin for the production of geopolymers. Geopolymers were prepared by mixing phosphate sludge with metakaolin or with fly ash in a proportion of 50 wt%. The effects of the main experimental factors (NaOH concentration, curing temperature and curing time) on the main physical characteristics (density, water absorption and compressive strength) were assessed using an experimental design of response surface methodology (DOE). The microstructure of geopolymer samples were investigated using X-ray diffraction, scanning electron microscopy and Fourier-transform infrared spectroscopy. Analysis of variance confirmed that the adopted DOE model described well the experimentally observed properties. The results of the microstructural analysis showed that the development of a gel-like phase was favored by the increase of sodium hydroxide concentration (from 8 to 14M) for the two kinds, fly ash and metakaolin-based geopolymers. The physical properties of the geopolymers indicated that an increase of temperature and NaOH concentration led to strengthen and dense materials, while the addition of phosphate sludge resulted in a reduction on the mechanical properties. However, substitution of fly ash by phosphate sludge resulted in strong specimens (62 MPa), which indicated that the use of phosphate mine tailings in geopolymers can be a viable technological solution for the sustainable management of these by-products. Highlights: Geopolymerization of phosphate sludge blended with metakoilin or fly ash. The factors effects on the microstructure and the measured properties were investigated. The physical properties were correlated to the processing factors.